Transhumance : papers from the International Association of Landscape Archaeology Conference, Newcastle upon Tyne, 2018 - Bowden, Mark,; Herring, Pete, (Access archaeology., 2021)
A collection of papers, mostly arising from the Newcastle and Durham conference of the International Association of Landscape Archaeology (2018), explore the practice, impact and archaeology of British and European transhumance, the seasonal grazing of marginal lands by domesticated livestock, usually accompanied by people, often young women.